2023
DOI: 10.3390/biom13050788
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies for Spinocerebellar Ataxia Type 1

Abstract: Spinocerebellar ataxia type 1 (SCA1) is an autosomal dominant neurodegenerative disorder that affects one or two individuals per 100,000. The disease is caused by an extended CAG repeat in exon 8 of the ATXN1 gene and is characterized mostly by a profound loss of cerebellar Purkinje cells, leading to disturbances in coordination, balance, and gait. At present, no curative treatment is available for SCA1. However, increasing knowledge on the cellular and molecular mechanisms of SCA1 has led the way towards seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 152 publications
0
1
0
Order By: Relevance
“… Chen D. et al (2022) also found that miR-504-3p was differentially upregulated in hTau mice. We found that miR-504-3p can target the ATXN1 gene, which has been extensively studied in NDs ( Kerkhof et al, 2023 ). Statistical analysis of relative expression results shows that ATXN1 gene expression was significantly downregulated ( p < 0.01) in Q74 ( Figure 4B ).…”
Section: Discussionmentioning
confidence: 93%
“… Chen D. et al (2022) also found that miR-504-3p was differentially upregulated in hTau mice. We found that miR-504-3p can target the ATXN1 gene, which has been extensively studied in NDs ( Kerkhof et al, 2023 ). Statistical analysis of relative expression results shows that ATXN1 gene expression was significantly downregulated ( p < 0.01) in Q74 ( Figure 4B ).…”
Section: Discussionmentioning
confidence: 93%